The Role of Financial Literacy in Reducing Tax Anxiety and Improving the Effectiveness of Tax Planning - Judijanto, Loso (Westscience Press, 2025)
This study investigates the role of financial literacy in reducing tax anxiety and improving the effectiveness of tax planning in Indonesia. Using a quantitative approach, data were collected from 78 individual taxpayers through a structured questionnaire. The analysis, conducted using SPSS version 26, revealed significant relationships among financial literacy, tax anxiety, and tax planning effectiveness. Financial literacy was found to positively influence tax planning effectiveness while reducing tax anxiety. Additionally, tax anxiety partially mediated the relationship between financial literacy and tax planning effectiveness. These findings emphasize the importance of financial education in fostering confident and effective tax planning behaviors among Indonesian taxpayers. The study provides actionable insights for policymakers to enhance tax compliance through targeted financial literacy initiatives and stress-reduction strategies.